IEEE Ultrasonics Symposium, 2005.
DOI: 10.1109/ultsym.2005.1603266
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of frequency dependent receive apodization

Abstract: To improve the directivity of a receive beamformer, the scalar apodization weigths are replaced by filters. For a frequency dependent apodization without changing the delay scheme of the dynamic receive beamformer, symmetric FIR filters are used. Different image quality measures are investigated and discussed that allow to quantify the dynamic range (contrast) and detail resolution of an ultrasound system by evaluation of the 2D point spread function. For an automated optimization of the apodization filter tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Schwann et al [2] used an assortment of resolution criteria to optimize frequency dependent receive apodization. Using a minimum sum squared error technique, Ranganathan and Walker [3] developed apodization functions for arbitrary system design. Sakhaei et al [4] produced apodization profiles that maximized the SNR of the beamformer output given a minimum sidelobe level in the lateral PSF.…”
Section: We Present Simulation Results Showing That Fir Filters Of Momentioning
confidence: 99%
“…Schwann et al [2] used an assortment of resolution criteria to optimize frequency dependent receive apodization. Using a minimum sum squared error technique, Ranganathan and Walker [3] developed apodization functions for arbitrary system design. Sakhaei et al [4] produced apodization profiles that maximized the SNR of the beamformer output given a minimum sidelobe level in the lateral PSF.…”
Section: We Present Simulation Results Showing That Fir Filters Of Momentioning
confidence: 99%
“…Recently, significant effort has been made to apply sophisticated algorithms to the reconstruction of medical ultrasound images. The methods range from using adaptive beamforming algorithms [10, 33], deconvolution techniques [3437], constrained and optimized receive apodization [2, 17, 38], to spatially matched filtered [3] beamformers. Other groups have investigated using statistical unbiased estimators [3, 11, 39] for ultrasound image reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Schwann et al suggested a similar type of architecture using linear phase FIR filters and also discussed the calculation of frequency dependent optimal receive apodization profiles. Their simulation results showed contrast improvements, however, their multiple objective formulation required iterative procedures and made it difficult to determine an "optimal" apodization profile [11]. Our formulation on the other hand requires no iterations and produces optimal apodization profiles in a least squares sense that maximize cystic resolution.…”
Section: Discussuionmentioning
confidence: 97%